Representaciones discursivas juveniles en prácticas escolares de escritura. (2016)
Studies on youth have grown substantially within the framework of inter- and transdisciplinary contributions. In this context, discourse studies are especially important as a field of analysis of the forms of representation of youth, since discourse is a social practice. This article examines which discursive representations about youth are emerging from written productions by students from a private educational institution in Tucumán, Argentina. It aims to make visible the youth problems and issues from the social subjects that are studied.